Hak Kepemilikan atas Satuan Rumah Susun di atas Tanah Hak Guna Bangunan yang Berdiri di atas Tanah Hak Milik - siti mutiah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Ownership of apartment is protected by law, so according to the concept of property rights, such ownership may be transferred and imposed warranty rights. The owner of Sarusun may sell the property to another party, or make it as collateral for the debt to the bank or other financial institution. Although the apartment is built on Hak Milik, Hak Guna Bangunan, and Hak Pakai on state land, the certificate still uses the name Certificate of Hak Milik Atas Satuan Rumah Susun, in contrast to the land title certificate in general which uses the name according to the status of the land right, such as Certificate of Hak Milik, Certificate of Hak Guna Bangunan, Certificate of Hak Guna Usaha, or Certificate of Hak Pakai